FROM EXPERIENCE OF CONDUCTING COMPARATIVE TESTS OF LOESS SOILS BY MANUAL DYNAMIC PROBES OF DIFFERENT CONSTRUCTIONS - Ulyanov, Y. V. (Science and Transport Progress, 2017)
Purpose. To determine the parameters of soils of loess formation, which are considered difficult in the construction or operation of housing and industrial facilities it is provided an analysis of the obtained field test data in order to use them in calculations to predict the situation, which can be complicated during operation of the facilities. The main purpose is: 1) improvement of our ideas about soils of loess formation using the example of determining possible changes in parameters of the loess mass, which is under load from the total weight of the structure; 2) testing the methodology of sounding by introducing improved manual probes: comparing the data of these studies with those obtained by other methods; 3) determination of the ways of further research using manual probes. Methodology. The directions of engineering-geological research were updated with the help of analysis and synthesis methods. Dynamic sounding was performed as a tool. Findings. The authors analyzed the data of dynamic sounding of soils by probes of the type DIIT-5 made by the Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT). Also, it was sounded the research object in difficult engineering-geological conditions: in a built-up area, the soil of which is represented by forests. The sounding was carried out using the small-sized LIATE probe. Further, the dynamic soil resistance to sounding was determined and the dependency formula between the obtained indices was derived. Originality. The sounding of the unwatered loess soils was carried out by light non-standard probe developed by the DNURT and, for comparison, by a self-developed probe of a group of authors, including the author of the article. The probe was used at the first time. Practical value. Dynamic sounding, which had spread significantly during engineering research in the construction of 60-70 years of the last century, is currently used rare. As for research of loess soils in their various states (watered, unwatered, disturbed and undisturbed, etc.) it is practically not developed. Therefore, the derivation of correlation formulas that confirm the rights to use existing formulas and design coefficients precisely for the loess mass (and this is about 90% of modern Quaternary soils of Ukraine) seems to be a topical subject.